Photocatalytically-assisted electrooxidation of herbicide fenuron using a new bifunctional electrode PbO2/SnO2-Sb2O3/Ti//Ti/TiO2. (July 2018) - Barbari, Karima; Delimi, Rachid; Benredjem, Zahia; Saaidia, Samia; Djemel, Abdelhak; Chouchane, Toufik; Oturan, Nihal; Oturan, Mehmet A.
Abstract: The degradation of the herbicide fenuron was investigated using a new porous bifunctional electrode where the electrooxidation takes place on one side and the photocatalysis on the other side. The characterization of the synthetized bifunctional electrode (PbO2 /SnO2 -Sb2 O3 /Ti//Ti/TiO2 ) was performed by scanning electron microscopy, energy dispersive X-ray spectrometry and X-ray diffraction analysis and showed that the anodic side (Ti/SnO2 -Sb2 O3 /PbO2 ) is covered with a tetragonal β-PbO2 film and that the photocatalytic side (Ti/TiO2 ) consists of an anatase phase of TiO2 . The single application of electrooxidation achieved 87.8% fenuron degradation and 84.1% chemical oxygen demand (COD) removal while heterogeneous photocatalysis resulted in only 59.2% and 39.7% fenuron concentration decay and COD removal, respectively. On the other hand, the photocatalytically-assisted electrooxidation (photo-electrooxidation) performed on the bifunctional electrode provided higher performances of fenuron degradation (97.5%) and mineralization (97.4%). Investigation of operating parameters highlighted the positive effect of increase in current density. Conversely, an increase in fenuron concentration led to a decrease in degradation rate and COD removal. It was also found that the COD removal and mineralization efficiency are higher in a neutral medium. Highlights: Preparation of a new bifunctional electrode: PbO2 /SnO2 -Sb2 O3 /Ti//Ti/TiO2 . Ti/SnO2 -Sb2 O3 /PbO2 anode exhibits better electrooxidation performances than PbO2 . Photocatalytically-assisted electrooxidation is more efficient than the two processes applied separately. Almost complete mineralization of fenuron by photo-electrooxidation under neutral pH conditions.